(untitled) (Third Sector Social Economic Review, 2017)
35% of the total conventional milk production area in Turkey is produced in the Aegean region. Izmir has been one of the highest milk production cities in Aegean region with a share of 22%. The main purpose of this study is to reveal the tendency of conventional dairy cattle farms to produce organic milk by way of the example of Tire in İzmir. Member farmers of S. S. Tire Milk Producers Cooperative were included in the research with the idea that the organization could positively affect organic milk production. There are currently 2093 farmers in the cooperative. The proportional sampling formula has been used in order to determine the number of the farmer that will be included in the content of the research. The sample volume was calculated as 90 % confidence interval and 10 % error margin according to the proportional sample volume formula. Sample size is calculated as 63. Data obtained from farmers face-to-face interviews using pre-arranged questionnaires constitute the primary material of the study. Furthermore, various data obtained from the institutions and organizations such as Turkish Statistical Institute, The Turkish Ministry of Food, Agriculture and Animal Husbandry. In addition, studies concerning with the subject in Turkey were also utilized. In the analysis of data, firstly socio-economic characteristics of the farms were examined. After that technical and economic analysis of dairy cattle farmers ( Number of milked goats, Lactation period, milk yield per animal, milk marketing and goat milk price received by the farmers, variable costs, gross production value and gross margin) were performed. Finally, level of knowledge and information sources of farmers related to organic milk production, attitude and behavior of farmers about organic milk production were examined. In this stage, a five-point Likert scale was used. According to the results of the research; 50.79% of the farmers are unknowledgeable, 38.10% of the farmers are less knowledgeable about organic milk production. While 50.79% of the farmers do not think organic dairy farming in the future, 34.92% of the farmers are undecided. 61.90% of the farmers state that government support is insufficient. While the main reason for farmers to think about organic milk production in the future is “high price and market guarantee”, the main reason for farmers not thinking organic milk production in the future is “high cost and inadequate capital""